Analysis of Steady State Cryogenic Air Separation Unit and Simulation of Fixed Bed Adsorption Separation of Air - Siddharth Ranjan Mohanty; Dr. A.M. Mohanty (International Journal of Engineering and Management Research, 2018)
Atmospheric dry air contains approximately 78% nitrogen, 21% oxygen, and 1% argon plus low concentrations of noble gases like carbon dioxide, hydrocarbons and other impurities. An air separation unit divides atmospheric air into the three pure gaseous components (nitrogen, oxygen and argon). Nitrogen, oxygen and argon are used by industry in large quantities and hence termed industrial gases. The current work aim is to simulate the cryogenic air separation unit including adsorber and cryogenic distillation. Simulation of absorber is carried out using ADSIM of Aspen Tech to remove carbon dioxide (CO2) and water vapour (H2O). The breakthrough curves of carbon dioxide (CO2) and water vapour on 5A molecular sieve and activated alumina respectively are found at different Reynolds number. The study helps to find out schedule time adsorber/desorber unit. ASPEN Plus simulator is used to simulate cryogenic air separation into nitrogen, oxygen and argon.